SELECTION OF THE MAIN DIRECTIONS OF PRODUCTION OF SMALL-SIZED EQUIPMENT USED IN MODERN SMALL-SIZED FARMS - Akhmedov Sh. A.; Rakhimboyeva D. S.; Kelginbayev A.A. (Academia Science Repository, 2023)
In this article, the selection of the main directions in the design of new types of small-scale agricultural machinery used in agricultural work in our country. Determining the main shortcomings of today's existing agricultural techniques. Determining the main priority areas of design work.